KRITIK HADIS TENTANG KEPEDULIAN ANAK TERHADAP ORANG TUANYA - Dr. Mukhlis Mukhtar (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Hadith about caring for children against parents, narrated by Imam Bukhari , Imam Muslim , Imam Abu Daud, Imam Turmuzi and Imam al - Nasai. With reference to kaedah validity of hadith which has been established by scholars, it was found that the tradition of caring children against parents, narrated by the narrators are generally siqah and matn hadith was also not found anything that could damage their quality. And thus it can be determined that the tradition is good quality authentic sanad and matan